(untitled) (Biological Sciences - PJSIR, 2022)
Only Penaeid postlarvae are available for coastal aquaculture ponds inBangladesh, an investigation wasmade from March 1988to Feb 1989.The data indicated that immigration of penaeid postlarvae takes place throughout the year in the Kutubdia channel. They were most abundant in April (301.91 indivs.rl Ofhrr’) when higher salinity condition (25.13%) also prevailed, and the minimum was recorded in Oct (6.17 indivs./IOOm»when the salinity was 13.25%. The postlarvai community of penaeid shirmps of this area was dominated by Penaeus indicus (15.35%); Punonodon (12.60%); P. scmisulcatus (8.24%); P. merguiensis (6.94%);and P. japonicus (4.13%). Their temporal and spatial distribution in the study area are presented here.